Kajian Yuridis mengenai Sengketa Wilayah antara China dan Indonesia di Perairan Natuna - Nofri Savira Putri (Universitas Muhammadiyah Jember, 2020)
Natuna Regency which is located in the Riau Island Province, is one of the region that has the potential of coastal and marine resources which are very potential to be developed. From that potential, illegal fishing and other violations conducted by foreign ships often happen in these water. One of them happened on January 1, 2020, China refuses the accusation of Indonesia for its fishing ships illegally entering Natuna Water. China claims that it has sovereignty in the South China Sea region closed to the Natuna Water. Whereas, the act of fishing is an act of theft that violates Indonesia's sovereign right over marine natural resources in the Indonesian Exclusive Economic Zone. This is based on the provisions of the United Nations Convention on the Law of the Sea (UNCLOS) 1982 and Constitution of the Republic of Indonesia No. 45/2009 about Amendment to Constitution No. 31/2004 about Fishery.